The normalization of Saudi law - Mallat, Chibli (New York, NY : Oxford University Press, 2022)
Saudi Arabia has never commanded more attention and yet it remains one of the world's least understood countries. In this book, Chibli Mallat dives into the heart of Saudi society, politics, and business by exploring the workings of its courts. Legal practitioners and scholars will find a comprehensive analysis of the law's operation in the kingdom. The practitioner will access full thematic coverage of all important fields: judicial organisation, contracts and torts, crime, family, property, administration, commerce, companies, banking, insolvency, the stock market, the constitution, succession, and human rights, with major statutes and a large number of court decisions distilled in 16 chapters. The scholar is presented with an assessment of a dynamic legal process, a 'normalization' of Saudi law where developing norms are both 'normal' (usual) and 'normative' (carrying moral force).
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Law -- Saudi Arabia; Law; Laws of specific jurisdictions & specific areas of law